2021
DOI: 10.1093/carcin/bgab006
|View full text |Cite
|
Sign up to set email alerts
|

Low-carbohydrate diets and the risk of pancreatic cancer: a large prospective cohort study

Abstract: Low-carbohydrate diets have become a popular approach for weight loss in recent years. However, whether low-carbohydrate diets are associated with the risk of pancreatic cancer remains to be elucidated. Hence, we examined the association of low-carbohydrate diets with the risk of pancreatic cancer in a US population. A population-based cohort of 95962 individuals was identified. A low-carbohydrate-diet score was calculated to quantify adherence to this dietary pattern, with higher scores indicating greater adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…Pancreatic cancer, a highly lethal malignancy, is the third most common cause of cancer‐related mortality in the United States, with an estimated 48 220 cancer deaths in 2021 1 . The exact mechanisms underlying pancreatic carcinogenesis remain elusive, but diets have been suggested to play a moderate role, 2 which are in line with our recent findings on dietary behaviors and pancreatic cancer 3‐5 . Ultra‐processed foods are industrial formulations mostly or completely manufactured with substances extracted from foods or additives (eg, starches, added sugars), with minimal or even no intact foods, 6 and are usually highly affordable, hyper‐palatable, ready‐to‐consume and energy‐dense.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Pancreatic cancer, a highly lethal malignancy, is the third most common cause of cancer‐related mortality in the United States, with an estimated 48 220 cancer deaths in 2021 1 . The exact mechanisms underlying pancreatic carcinogenesis remain elusive, but diets have been suggested to play a moderate role, 2 which are in line with our recent findings on dietary behaviors and pancreatic cancer 3‐5 . Ultra‐processed foods are industrial formulations mostly or completely manufactured with substances extracted from foods or additives (eg, starches, added sugars), with minimal or even no intact foods, 6 and are usually highly affordable, hyper‐palatable, ready‐to‐consume and energy‐dense.…”
Section: Introductionsupporting
confidence: 58%
“…A hospital‐based case‐control study, involving 307 pancreatic cancer cases and 322 controls, revealed a positive association between intake frequency of bread and the risk of pancreatic cancer (odds ratio >7 vs ≤7 times per week: 1.50; 95% CI: 1.05‐2.13), 42 which is consistent with our results. As cereal foods mentioned above are a poor source of dietary fiber but a rich source of carbohydrates, thus it is possible that the adverse influence of high cereal consumption on the risk of pancreatic cancer is mainly attributable to its low content of dietary fiber and high content of carbohydrate, given that high dietary fiber intake 43 and adherence to low‐carbohydrate diets 5 are associated with a reduced risk of pancreatic cancer. Intuitively, this explanation seems to be contradictory to the observations that subjects in the highest vs the lowest quartiles of ultra‐processed food consumption had a somewhat higher intake of dietary fiber in our study population (19.6 ± 7.7 vs 18.0 ± 9.0 g/day; Table 1) and that ultra‐processed food consumption was positively associated with the risk of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic cancer is the third most common cause of cancer-related mortality in the US, with an estimated 48,220 cancer deaths in 2021 ( 10 ). Diets have been indicated to play an important role in the etiology of this cancer ( 11 ), which is in accordance with our recent findings on dietary behaviors and pancreatic cancer ( 12 14 ). The association of fried food consumption with the risk of pancreatic cancer has been evaluated in an early case-control study in Canada, with a positive association observed ( 15 ).…”
Section: Introductionsupporting
confidence: 92%
“…Despite that the specific molecular mechanisms for pancreatic carcinogenesis remain to be elucidated, however, dietary habits have been suggested to play a moderate role [2,3]. Indeed, our group recently found that low-carbohydrate diets conferred a lower risk of pancreatic cancer in a cohort of 95,962 American adults [4]. Identifying more dietary patterns in relation to the risk of pancreatic cancer may facilitate the prevention of this cancer.…”
Section: Introductionmentioning
confidence: 96%